Investigating the Relationship Between Physical Education Teachers' Perceptions, Technological Knowledge and Classroom Management Profiles - Çar, Bekir; Sural, Volkan; Güler, Hasan (Asian Institute of Research, 2022)
Overcoming the technology barrier is critical to integrating technology and education. Emerging and changing technologies are rapidly impacting individuals' daily lives as well as their educational lives. The concept of technostress seems to be associated with technological pedagogical field knowledge and classroom management profiles. This study also aims to determine if there is a relationship between PE and physical education teachers' technostress levels, technological pedagogical knowledge, and classroom management profiles. 275 PE and physical education teachers working in Ankara province participated in the study. Data collection was done using the scale to determine teachers' technostres level, technological-pedagogical knowledge and class management profile. The levels of technostres and technological-pedagogical knowledge did not differ significantly by gender, educational status, sport type, place of graduation, age, professional seniority, and time of technology use of physical education teachers. When examining classroom management profiles, there were differences by gender, educational status, athletic department, and age group, but no significant differences between place of graduation, professional seniority, and time of technology use. When examining the class management profiles by gender variable, it was found that female teachers are on the peripatetic and ignorant profile compared to males, by educational level of graduates and in the scatter profile, those who are in the athletic department in the individual sports do not match those in the team sports department in the profile, and in the age group of 24-34 years old were highly rated by the class management profiles in the 35-44 years old category. As a result, it was found that there is an excellent level of significant relationship between the perception of technostars and class management profiles of physical education teachers, in a negative way, while there is a non-significant relationship between Tpba and technostars, with class management and Tpba being positive.